Effects of Reactive Red 239 on Developing Zebraﬁ sh (Danio rerio) Embryos - Jungtanasombut, Waraporn; Preeprem, Pichapop; Kovitvadhi, Satit; Kovitvadhi, Uthaiwan; Hannongbua, Supa (Agriculture and Natural Resources, 2014)
The acute effects of the well-known and widely used mono azo-dye, Reactive Red 239 (RR 239) were investigated using the sixth cleavage stage of zebraﬁ sh embryos as a biological experimental model. Toxicity was evaluated through three endpoints—survival rate, hatching rate and normality of embryo development. In order to ﬁ nd the key parameter relating to survival of RR 239-exposed embryos, the relationships between survival and concentration or malformations were studied using a cuboidal equation and multiple linear regression. The results revealed that exposure to RR 239 during 96 hr gave a median lethal concentration value of 1,579 ± 25 mg.L-1 which could lead to the classiﬁ cation of RR 239 as a nontoxic textile dye for aquatic organisms and was expressed as an effective concentration value of 1,536 ± 36 mg.L-1 for the assay. However, exposure to RR 239 with a higher concentration than 500 mg.L-1 reduced the embryonic survival rate as well as the hatching rate on the one hand and stimulated various morphological malformations on the other hand. Cuboidal equations showed that the concentration, yolk sac edema and hatching play important roles in survival, with hatching having the greatest effect of these factors. The results indicated that the probable effects of released efﬂ uent containing RR 239 on natural aquatic organisms should be further explored.